THE IMPORTANCE OF AGRICULTURAL PRODUCTION IN ENSURING FOOD SECURITY IN UZBEKISTAN (Marketing Journal, 2025)
This article analyzes the importance of agricultural production in ensuring food security in Uzbekistan. The measures taken to reform agriculture, develop market relations, attract investment in the industry, and introduce resource -saving technologies are considered. The study examines the international experience and financial condition of local agricultural enterprises, as well as suggests effective ways t o ensure food security in Uzbekistan.
Keywords: food security; agriculture; export; investment; innovation; competitiveness